2008
DOI: 10.1038/nature07590
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of phototaxis in marine zooplankton

Abstract: The simplest animal eyes are eyespots composed of two cells only: a photoreceptor and a shading pigment cell. They resemble Darwin's 'proto-eyes', considered to be the first eyes to appear in animal evolution [1][2][3][4] . Eyespots cannot form images but enable the animal to sense the direction of light. They are characteristic for the zooplankton larvae of marine invertebrates and are thought to mediate larval swimming towards the light. Phototaxis of invertebrate larvae contributes to the vertical migration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
342
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 268 publications
(350 citation statements)
references
References 29 publications
4
342
3
1
Order By: Relevance
“…We observed that the branched axons are full of large dense-cored vesicles (Fig. 3H), but are completely devoid of synapses that are typical for cells containing classical neurotransmitters (45), indicating that these MIP chemosensory neurons signal exclusively via the release of neuropeptides.…”
Section: Mip Triggers Larval Settlement In Platynereismentioning
confidence: 90%
See 1 more Smart Citation
“…We observed that the branched axons are full of large dense-cored vesicles (Fig. 3H), but are completely devoid of synapses that are typical for cells containing classical neurotransmitters (45), indicating that these MIP chemosensory neurons signal exclusively via the release of neuropeptides.…”
Section: Mip Triggers Larval Settlement In Platynereismentioning
confidence: 90%
“…4A). The activation was specific, as 12 other Platynereis neuropeptides (19,45) did not activate the MIP receptor (Fig. 4B).…”
Section: Mip Triggers Larval Settlement In Platynereismentioning
confidence: 98%
“…For example, the cyclopean field of view (i.e., combined field of view of both eyes [26]) of the grey-headed Albatross is about 270 • in the horizontal plane [27], and that of Dasyatis sabina fish is about 327 • in the horizontal plane [26]. This kind of restricted view of the neighborhood also plays a role in the phototactic motion of certain marine organisms such as Platynereis larvae [28]. Thus exploration of the effects of limitation of the angular range of interaction neighborhood should be of interest in the study of all those processes where the Vicsek model is relevant.…”
Section: Introductionmentioning
confidence: 99%
“…This reduction in swimming activity is interpreted as a decrease in ciliary movement caused by exposure to the treatments. While this is the first evidence of such an effect on larval behavior for this species, previous studies have investigated the neuronal control of larval ciliary movement in a number of mollusc species and considerable efforts have been made to characterize and map the neural circuit architectures involved (Jékely et al 2008). Results from these studies frequently reveal that patterns of cilia-based locomotion, velar ciliary beat frequency and the rate and duration of ciliary arrests are under dual innervation by excitory serotonergic and inhibitory dopaminergic mechanisms ( Croll & Dickinson 2004;Braubach et al 2006;Croll 2009).…”
Section: Discussionmentioning
confidence: 99%